초음파로 진단된 비알코올 지방간 환자에서 Cytokeratin-18과 대사 지표와의 상관관계 - 곽동신; Dong Shin Kwak; 전대원; Dae Won Jun; 조영균; Yong Kyun Cho; 이승민; Seung Min Lee; 이세환; Se Hwan Lee; 정인섭; In Sub Jung; et al. (The Korean journal of gastroenterology, 2014)
목적: 이번 연구에서는 비알코올 지방간 환자에서 CK-18과 대사지표 및 대량 영양 조성과의 연관성을 연구하고자 하였다. 대상 및 방법: 3개 병원의 소화기내과와 검진센터에 방문한 106명의 비알코올 지방간 환자와 106명의 정상대조군을 대상으로 신체 계측 및 기본 혈액 검사와 CK-18 검사를 시행하였고 각 군에서 대사지표, 대량 영양조성과 CK-18과의 상관관계를 분석하였다. 결과: 비알코올 지방간 환자에서 정상대조군에 비해 CK-18 수치가 의미 있게 높았으며 CK-18은 수축기 혈압, AST, ALT 와 양의 상관관계를, 고밀도 콜레스테롤과는 음의 상관관계를 보여 주었다. 또한 비알코올 지방간 환자를 대사증후군이 동반되어 있는 환자와 그렇지 않은 환자로 나누어 비교하였을 때에 동반되어 있는 환자에서 CK-18이 더 상승되어 있었으며 CK-18을 400 U/L 이하 군과 초과 군으로 나누었을 때에 400 U/L 초과 군이 더 높은 체질량지수와 복부 피하지방, AST, ALT를 보여주었다. 또한 칼로리 섭취율이 높을수록, 탄수화물 섭취율이 높을수록 CK-18이 높은 결과를 보여 주었다. 결론: 이번 연구에서 CK-18은 정상대조군과 비교하여 초음파로 진단된 비알코올 지방간 환자에서 의미 있게 높았다. 또한 비알코올 지방간 환자에서 혈청 CK-18 농도가 400 U/L을 넘는 경우 복부비만, 대사증후군 및 간 염증 수치 상승과 매우 밀접한 연관성을 보였다. Background/Aims: The serum cytokeratin-18 (CK-18) has been suggested to be a surrogate marker of non-alcoholic fatty liver disease (NAFLD). The aim of this study was to investigate the correlation between CK-18 and metabolic parameter in NAFLD patients. Correlation between CK-18 and macronutrient composition was also assessed. Methods: A total of 212 subjects were recruited. Blood chemistry including fasting glucose, cholesterol level, AST, ALT, and CK-18 were compared. Data on calorie intake and carbohydrate consumption were acquired by five-day-diet diary using 24 hour recall method. Results: Plasma CK-18 were markedly increased in patient with NAFLD compared with control group (420.4±282.3 vs. 313.6±179, p＜0.001). Plasma CK-18 were positively correlated with systolic blood pressure (r=0.130), ALT (r=0.503) and negatively correlated with HDL cholesterol (r=-0.246). NAFLD patients with metabolic syndrome had higher CK-18 level than those without metabolic syndrome (484.0 vs. 372.1 U/L, p=0.021). When NAFLD patients were subdivided into two groups with CK-18 cut-off value of 400 U/L, patients with CK-18 level over 400 U/L showed higher body mass index (28.0±4.5 vs. 25.5±4.3), subcutaneous abdominal fat (283.5±172.2 vs. 195.7±147.8), AST (52.7±26.3 vs. 40.7±23.5) and ALT (102.0±52.6 vs. 61.2±32.2). Calorie intake (r=0.301) and carbohydrate intake (r=0.305) also showed positive correlation with CK-18. Conclusions: Plasma CK-18 showed positive correlation with metabolic parameters as well as calorie and carbohydrate intake when its cut-off value of greater than 400 U/L was used. (Korean J Gastroenterol 2014;64:206-212)